Recent Progress in Crystallographic Characterization, Magnetoresponsive and Elastocaloric Effects of Ni-Mn-In-Based Heusler Alloys—A Review - Yan, Hai-Le; Huang, Xiao-Ming; Esling, Claude (Frontiers in Materials, 2022)
Ni-Mn-In-based magnetic shape memory alloys have promising applications in numerous state-of-the-art technologies, such as solid-state refrigeration and smart sensing, resulting from the magnetic field-induced inverse martensitic transformation. This paper aims at presenting a comprehensive review of the recent research progress of Ni-Mn-In-based alloys. First, the crystallographic characterization of these compounds that strongly affects functional behaviors, including the crystal structure of modulated martensite, the self-organization of martensite variants and the strain path during martensitic transformation, are reviewed. Second, the current research progress in functional behaviors, including magnetic shape memory, magnetocaloric and elastocaloric effects, are summarized. Finally, the main bottlenecks hindering the technical development and some possible solutions to overcome these difficulties are discussed. This review is expected to provide some useful insights for the design of novel advanced magnetic shape memory alloys.